Painful diabetic peripheral neuropathy: Health care costs and complications from 2010 to 2015. Issue 1 (February 2020) - Kiyani, Musa; Yang, Zidanyue; Charalambous, Lefko T.; Adil, Syed M.; Lee, Hui-Jie; Yang, Siyun; Pagadala, Promila; Parente, Beth; Spratt, Susan E.; Lad, Shivanand P.
Abstract : Objective: To quantify health care resource utilization and risk of complications in painful diabetic peripheral neuropathy (pDPN). Methods: Adult patients diagnosed with diabetes mellitus or diabetic peripheral neuropathy (DPN) were identified in MarketScan from January 2010 to December 2015. Subgroups (pDPN and nonpainful DPN) were based on the use of pain medications 6 months before a new indexed diagnosis and 1 year thereafter. Health care costs were collected for up to 5 years, and complications charted for those with at least 1 and 2 years of follow-up. Complication comparisons were made using χ 2 or Fisher exact tests, and a multivariable regression cost model was fit with log link function using generalized estimating equations. Results: Among 360, 559 patients with diabetes (62 ± 14 years; 54.3% female), 84, 069 (23.3%) developed pDPN, 17, 267 (4.8%) experienced nonpainful DPN, and the majority (259, 223, 71.9%) were controls with diabetes without neuropathy. At baseline, costs associated with pDPN patients were 20% higher than diabetic controls (95% confidence interval [CI] [1.19, 1.21], p < 0.001), which increased to 31% in the 5th year (95% CI [1.27, 1.34], p < 0.001). Patients with pDPN had 200%, 356%, and 224% of the odds of using opioids, anticonvulsants, and antidepressants, respectively, compared with diabetic controls. The amputation risk in the pDPN subgroup was 16.24 times that of diabetic controls (95% CI [2.15, 122.72], p = 0.0003), and 87% more patients with pDPN experienced lower extremity infections (95% CI [1.43, 2.46], p < 0.0001) within a year. Within 2 years, 2.2% of patients with pDPN had falls and fall-related injuries compared with 1.1% of diabetic controls ( p < 0.0001). Conclusions: Our study characterizes a substantial pDPN cohort in the United States, demonstrating considerable morbidity and economic costs.